ANALISIS TINGKAT PROFITABILITAS DALAM MENINGKATKAN KINERJA PADA PT. UNILEVER INDONESIA, Tbk - Raden Mia Okinawati Syafitri (Journal Accounting International Mount Hope, 2024)
This research was carried out to identify and analyze the level of profitability in improving performance at Unilever Indonesia, Tbk in the year 2020 s.d. 2023 based on the ratio of Gross Profit Margin, net profit margin, and Return on Asset. The results of this study showed that the Gross Profit Margin and Return on Asset ratio of Unilever Indonesia, Tbk was categorized as “Good” because the ratio value was above the industry average. However, for the Net Profit margin ratio, Unilevers Indonesia was still below the industrial average, showing that the poor performance of the company and the less efficient operational activities of the firm.